If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -2) = 4y Reorder the terms: 8(-2 + x) = 4y (-2 * 8 + x * 8) = 4y (-16 + 8x) = 4y Solving -16 + 8x = 4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 8x = 16 + 4y Combine like terms: -16 + 16 = 0 0 + 8x = 16 + 4y 8x = 16 + 4y Divide each side by '8'. x = 2 + 0.5y Simplifying x = 2 + 0.5y
| 4x+20=7x-25 | | -2(p-2)=-2(1-2p) | | -14-z/9=-12 | | 2(10+x)=90 | | 31=6+12+c | | 10x+1-2x=3+8x-10 | | -11=-5(3k+8)+8(-5-k) | | 4(2x-3)=x+9 | | -6(-6n+7)-7=-157 | | 12x-1=-7 | | 3-4(x-3)=3(x-6)-7x | | -21w+5+4w-1= | | 6(-4-x)=-18x | | 0.4x+3=-0.2x-0.6 | | 5x+5=3x+4+2x+1 | | x^2+bx+6.25=0 | | 90=2x+10 | | X+y=122 | | -3(4+3)=2y+3 | | 17-3=4x | | -3(q-7)=2+q-21 | | 2x+1=2(x-4) | | 3x^5/6-16=80 | | 2x+1=2(x-8) | | x-5+4x+x+x-8=360 | | 3x-7(x+6)=14 | | 2/3x=1=-1/3x-1 | | 20(-9+6)=-6(x-2) | | 4(3-z)-36=26z-6(4+5z) | | y=c(x-2) | | 4sin^2x+11sinx-3=0 | | 4(3+x)=-4-x |